Waqf-Based Crowdfunding: A Case Study of Waqfworld.Org - Alma’amun, Suhaili; Mohd Shafiai, Muhammad Hakimi; Shahimi, Shahida; Ahmad Adnan, Muhammad Syaukani (International Journal of Islamic Economics and Finance Research, 2020)
The traditional approach of managing waqf has been transformed into something that is more in line with the fast-moving world of financial technology (fintech) such as e-waqf or online cash waqf. This paper brings different view of what fintech can offer to empower waqf beyond the typical e-waqf. It is called crowdfunding. Crowdfunding is the process of raising money using an online platform to fund good causes, be it business venture or social causes. Using Waqfworld.org as a case study, this paper delineates the process of establishment of Waqfworld.org as the first waqf-based crowdfunding. It elaborates the challenges and issues pertaining to the Waqfworld.org. Findings from this study are useful for others should they decide to set up similar type of crowdfunding platform or any Islamic crowdfunding platform within the social Islamic finance areas.